Continuous morphological variation correlated with genome size indicates frequent introgressive hybridization among Diphasiastrum species (Lycopodiaceae) in Central Europe - Hanušová, Kristýna; Ekrt, Libor; Vít, Petr; Kolář, Filip; Urfus, Tomáš (PloS one, 2014)
Introgressive hybridization is an important evolutionary process frequently contributing to diversification and speciation of angiosperms. Its extent in other groups of land plants has only rarely been studied, however. We therefore examined the levels of introgression in the genus Diphasiastrum, a taxonomically challenging group of Lycopodiophytes, using flow cytometry and numerical and geometric morphometric analyses. Patterns of morphological and cytological variation were evaluated in an extensive dataset of 561 individuals from 57 populations of six taxa from Central Europe, the region with the largest known taxonomic complexity. In addition, genome size values of 63 individuals from Northern Europe were acquired for comparative purposes. Within Central European populations, we detected a continuous pattern in both morphological variation and genome size (strongly correlated together) suggesting extensive levels of interspecific gene flow within this region, including several large hybrid swarm populations. The secondary character of habitats of Central European hybrid swarm populations suggests that man-made landscape changes might have enhanced unnatural contact of species, resulting in extensive hybridization within this area. On the contrary, a distinct pattern of genome size variation among individuals from other parts of Europe indicates that pure populations prevail outside Central Europe. All in all, introgressive hybridization among Diphasiastrum species in Central Europe represents a unique case of extensive interspecific gene flow among spore producing vascular plants that cause serious complications of taxa delimitation.
Keywords: Genetic Markers; biologická evoluce; Genome, Plant; diploidie; ekosystém; délka genomu; Diploidy; křížení genetické; Europe; Crosses, Genetic; Evropa; Plant Leaves; genom rostlinný; Genome Size; genetická variace; Biological Evolution; Lycopodiaceae; Plant Stems; DNA, Plant; stonky rostlin; Genetic Variation; Spores; plavuňovité; spory; DNA rostlinná; Species Specificity; Hybridization, Genetic; hybridizace genetická; druhová specificita; genetické markery; Ecosystem; listy rostlin